Experimental Study: Financial Literacy and Financial Efficacy of Interest in Investing - Zainuddin Zainuddin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This research was conducted to determine students' level of literacy and financial efficacy on their interest in investing in the capital market using a quantitative method with experimental research. The treatment in this study is the socialization of the capital market with material related to an overview of investment in the Indonesian capital market, explanation of stocks and stock trading mechanisms, explanation of investor identity cards, and explanation of opening a stock account. This research was conducted at universities in Ternate City that already have the Indonesia Stock Exchange Gallery with a sample of students who have passed intermediate financial accounting courses and have learned basic investment knowledge. The contribution of this research is to provide capital market socialization to students so that they have an interest in investing in the capital market by knowing the basics of financial literacy and efficacy. This research design is quantitative research conducted on students in North Maluku with a total sample of 150 respondents. The data were obtained through experimental tests through research questionnaires, separating the control class from the experimental class and providing the capital market socialization treatment to the experimental class. The data analysis method used is the independent sample t-test, with the Mann Whitney test. The results showed that 1). There is no significant difference in the mean score of student financial literacy in the control and experimental classes; 2). There is a significant difference in the average value of Student Financial Efficacy in the control and experimental classes; 3). There is a significant difference in the average value of student interest in investing in the capital market in the control and experimental classes.